2020
DOI: 10.17306/j.jard.2020.01304
|View full text |Cite
|
Sign up to set email alerts
|

Economic viability of onion production in the commune of Grand-Popo, Republic of Benin

Abstract: This study estimated the profitability and the level of technical efficiency of the onion farms. It also identified factors that contribute to technical efficiency in onion production. Data were collected from 180 randomly selected onion farms using a pretested interview schedule. Partial budgeting techniques and the stochastic production frontier were modeled for data analysis. Profitability indices revealed a value of 0.771 and 0.280 for operating ratio and return to capital invested respectively. The mean t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Several studies conducted at global, national, and regional levels have investigated factors influencing onion production, productivity, and technical efficiency. These studies include [11,14,15,17,[19][20][21][22][23][24][25][26][27][28] and [29]. The studies mentioned above have found that factors such as gender, age, education level, household size, onion purchasing quantity, production experience, land area allocated to onion cultivation, extension services, storage facilities, coordination among producers, access to fertilizers and quality seeds, irrigation services, diseases and pests, plant spacing, soil fertility management practices, and access to credit significantly influence onion production.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies conducted at global, national, and regional levels have investigated factors influencing onion production, productivity, and technical efficiency. These studies include [11,14,15,17,[19][20][21][22][23][24][25][26][27][28] and [29]. The studies mentioned above have found that factors such as gender, age, education level, household size, onion purchasing quantity, production experience, land area allocated to onion cultivation, extension services, storage facilities, coordination among producers, access to fertilizers and quality seeds, irrigation services, diseases and pests, plant spacing, soil fertility management practices, and access to credit significantly influence onion production.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we hypothesized that large family members, male headed households, educated farmers, obtaining access to irrigation, modern inputs, credit, extension service, and being a member of farm cooperative contribute in the operation of farm activities of onion. Farmers who have an oxen enables them to manage their farm lands, and experienced farmers have better administrative abilities that they can exert to their onion production [11,14,15,17,[19][20][21][22][23][24][25][26][27][28] and [29]. The socioeconomic variables examined in this study include gender, age, education, labor force, off-farm income, and the number of oxen owned.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Several studies conducted at global, national, and regional levels have investigated factors influencing onion production, productivity, and technical efficiency. These studies include [11,14,15,17,[19][20][21][22][23][24][25][26][27][28] and [29]. The studies mentioned above have found that factors such as gender, age, education level, household size, onion purchasing quantity, production experience, land area allocated to onion cultivation, extension services, storage facilities, coordination among producers, access to fertilizers and quality seeds, irrigation services, diseases and pests, plant spacing, soil fertility management practices, and access to credit significantly influence onion production.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we hypothesized that large family members, male headed households, educated farmers, obtaining access to irrigation, modern inputs, credit, extension service, and being a member of farm cooperative contribute in the operation of farm activities of onion. Farmers who have an oxen enables them to manage their farm lands, and experienced farmers have better administrative abilities that they can exert to their onion production [11,14,15,17,[19][20][21][22][23][24][25][26][27][28] and [29]. The socioeconomic variables examined in this study include gender, age, education, labor force, off-farm income, and the number of oxen owned.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Several studies conducted at global, national, and regional levels have investigated factors influencing onion production, productivity, and technical efficiency. These studies include [11,14,15,17,[19][20][21][22][23][24][25][26][27][28] and [29]. The studies mentioned above have found that factors such as gender, age, education level, household size, onion purchasing quantity, production experience, land area allocated to onion cultivation, extension services, storage facilities, coordination among producers, access to fertilizers and quality seeds, irrigation services, diseases and pests, plant spacing, soil fertility management practices, and access to credit significantly influence onion production.…”
Section: Introductionmentioning
confidence: 99%